2013
DOI: 10.2337/db12-1430
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Locations of Human Brown Adipose Tissue

Abstract: We will review information about and present hypotheses as to the anatomy of brown adipose tissue (BAT). Why is it located where it is in humans? Its anatomical distribution is likely to confer survival value by protecting critical organs from hypothermia by adaptive thermogenesis. Ultimately, the location and function will be important when considering therapeutic strategies for preventing and treating obesity and type 2 diabetes, in which case successful interventions will need to have a significant effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(166 citation statements)
references
References 47 publications
(103 reference statements)
3
159
0
4
Order By: Relevance
“…For areas of WAT, gluteal fat depots were evaluated because they are definable in every patient, and we expected to find exclusively WAT in the gluteal fat depots (3,29). For every dataset with 18 F-FDG-avid supraclavicular fat depots, regions of interest (ROIs) were placed in the PET dataset bilaterally into the supraclavicular fat depots, automatically delineating the shape of the 18 F-FDG-avid fat depots (50% isocontour).…”
Section: Image Analysismentioning
confidence: 99%
“…For areas of WAT, gluteal fat depots were evaluated because they are definable in every patient, and we expected to find exclusively WAT in the gluteal fat depots (3,29). For every dataset with 18 F-FDG-avid supraclavicular fat depots, regions of interest (ROIs) were placed in the PET dataset bilaterally into the supraclavicular fat depots, automatically delineating the shape of the 18 F-FDG-avid fat depots (50% isocontour).…”
Section: Image Analysismentioning
confidence: 99%
“…101 Humans also possess various small BAT depots including around organs such as kidney and heart, and in other subcutaneous depots such as under the arms. 98,102 Whether or not humans can boost their available BAT mass was previously unclear, but two recent studies have demonstrated that cold acclimation in humans, after repeated daily cold exposure, elevates BAT volume and activity, and increases energy expenditure. 103,104 In additional, mice are often housed at a room temperature that is not thermoneutrality for them, forcing them to undergo thermogenesis at room temperature in order to maintain their body temperature.…”
Section: Human Vs Mouse Batmentioning
confidence: 99%
“…Because developmental lineage tracing is not possible in humans, debate continues about the "brownness" of human adipose depots [15,16]. However, it is becoming increasingly clear that a number of human adipose depots have characteristics somewhere on the spectrum of beige/brite fat, including perivascular fat, epicardial fat, and the fat surrounding the kidneys, pancreas, and liver [17]. In addition to their more systemic roles in thermogenesis and whole-body energy metabolism, these depots are thought to contribute locally to the metabolic health and function of the tissues they surround [18,19].…”
Section: Introductionmentioning
confidence: 99%